2020
DOI: 10.1371/journal.ppat.1008874
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring links between vitamin D deficiency and COVID-19

Abstract: Coronavirus Disease 2019 (COVID-19) pandemic remains a major public health threat in most countries. The causative severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus can lead to acute respiratory distress syndrome and result in mortality in COVID-19 patients. Vitamin D is an immunomodulator hormone with established effectiveness against various upper respiratory infections. Vitamin D can stall hyper-inflammatory responses and expedite healing process of the affected areas, primarily in the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(139 citation statements)
references
References 37 publications
1
126
1
11
Order By: Relevance
“…Most of these studies have indicated a significant association between vitamin D deficiency and severe clinical outcomes of COVID-19 [31,32]. Age, sun exposure, and diet are the main risk factors for vitamin D deficiency and considering these factors, several studies have been conducted to evaluate the possible link between these factors and the clinical outcomes of COVID-19 [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have indicated a significant association between vitamin D deficiency and severe clinical outcomes of COVID-19 [31,32]. Age, sun exposure, and diet are the main risk factors for vitamin D deficiency and considering these factors, several studies have been conducted to evaluate the possible link between these factors and the clinical outcomes of COVID-19 [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D supplementation is a relatively cheap, available and safe measure. However, there is no solid scientific evidence to support the routine clinical use of vitamin D in COVID-19 patients [ 163 ].…”
Section: Vitamin D In the Coronavirus Disease-19 (Covid-19) Eramentioning
confidence: 99%
“…All authors indicated that deficient vitamin D levels (range [? ]30 ng / ml) are associated with a higher risk of Covid-19 infection and more severe clinical outcomes, in particular one study 28 showed that this problem is particularly frequent with a prevalence in 50% of the population of over 40 countries which has levels below 50% with peaks of 70% in nations such as India, vice versa having serum levels between 40 and 60 ng / ml proves to be a more protective factor against the infection and its outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, vitamin D deficiency appears to be a frequent condition, in over 40 countries, levels of vitamin D deficiency were detected in 50% of the population analyzed 28 , demonstrating that vitamin D supplementation plays a relevant role in the treatment of this pathology 29 .…”
Section: Resultsmentioning
confidence: 99%